Análisis Multitemporal Del Cuerpo De Agua Del Embalse Tominé, En El Departamento De Cundinamarca, Para El Período 1977 – 2023 (2024)
The multi-teemporal Analysis of Tomine reservoir was made to found the variations in a long period of time, it was determined the area of Tominé reservoir, located in the department of Cundinamarca, in Colombia, presented important variations within the period between 1977 and 2023. with the processing of Landsat satellite images from different years and Through the use of aerial photographs of IGAC origin for the year 2007, the water mirror of the reservoir and the surfaces covered with aquatic vegetation (water hyacinth) were identified and digitized. The editing and analysis process was carried out through ArcMap 10.8.1 Software.